Funkcionalna diagnostika karateistov - Zemkova, E.; Dzurenkova, D. (Kinesiologia Slovenica, 2004)
The paper deals with functional diagnostic of karate athletes in different ages by means of the laboratory tests. The results of long-term studies showed as a suitable method for the assessment of multi choice reaction time the agility test, for explosive power of lower limbs a ten and sixty-second tests on the jump ergometer, for strength a ten-second test on the isokinetic cycle ergometer, for anaerobic abilities a thirty-second load on the treadmill in the form of tethered running, and for aerobic capabilities the spiroergometric examination. Such an evaluation of sport performance in karate athletes based on functional tests can contribute to more effective training planning with subsequent enhancement of their performance.